Sharia Bank Marketing Communication Strategies in Increasing Brand Awareness (Study on Islamic Bank in Yogyakarta City) - Syarif As'ad (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2020)
Building brand awareness in the community is an essential task of a marketing agent. With increased brand awareness, companies can easily create consumer loyalty, which leads to profits from the company. This study aims to describe the pattern of marketing communication strategies that have been carried out by the management of Islamic banks in the city of Yogyakarta in order to increase the brand awareness of the people of the city of Yogyakarta. The informants of this study were 35 employees from 11 Islamic banks in the city of Yogyakarta and the banking supervisor (OJK), using purposive and snowball sampling techniques through structured interviews and questionnaires. The results of this study describe the marketing communication strategy of Islamic banking carried out to reach the layers of society in the city of Yogyakarta through location-based mapping, which includes shopping centers, office complexes, housing, educational institutions, tourist objects, restaurants, around places of worship, and other crowd centers. Other forms of mapping are based on socio-religious organizations such as Muhammadiyah and Nahdlotul Ulama and economic class. In addition, this study also examines the integrated marketing communication strategy that has been implemented by Islamic banks in the city of Yogyakarta through advertisements, sales promos, events and experiences, public relations and publicity, direct marketing, interactive marketing, word of mouth, and personal selling with the aim of achieving brand awareness.